2019
DOI: 10.4103/jmu.jmu_15_19
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings in superficial angiomyxoma of the vulva in a perimenopausal female

Abstract: Superficial angiomyxoma (SAM) is an extremely rare soft tissue tumor. It is especially rare in the vulva, with only a few such cases reported in the medical literature. Here, we report a case of SAM of the vulva that was initially suspected to be a Bartholin gland cyst. The patient underwent local excision of the vulvar cyst under lumbar anesthesia. Clinical manifestations and B-scan ultrasonographic features are similar between SAM and cysts. Echoes in the mass are uneven and exhibit low echoes and punctate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…US showed that the single mass was oval, well‐circumscribed, heterogeneous, and exhibited low echo and punctate hyperechoic variable position with slight posterior enhancement. Unlike the ultrasonic feature of SAM in the scrotum, CDI revealed that blood flow signal was abundant inside vulvar SAM 2 . Therefore, large cohorts are needed to further explore ultrasonic features of scrotal SAM on US.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…US showed that the single mass was oval, well‐circumscribed, heterogeneous, and exhibited low echo and punctate hyperechoic variable position with slight posterior enhancement. Unlike the ultrasonic feature of SAM in the scrotum, CDI revealed that blood flow signal was abundant inside vulvar SAM 2 . Therefore, large cohorts are needed to further explore ultrasonic features of scrotal SAM on US.…”
Section: Figurementioning
confidence: 97%
“…Unlike the ultrasonic feature of SAM in the scrotum, CDI revealed that blood flow signal was abundant inside vulvar SAM. 2 Therefore, large cohorts are needed to further explore ultrasonic features of scrotal SAM on US. SAM should also be distinguished from another rare type of scrotal tumor-aggressive angiomyxoma (AAM).…”
Section: Funding Informationmentioning
confidence: 99%
“…Palpation of SAM reveals a soft, mobile, nonulcerated, and well‐defined tumor, with a range of polypoid to papulonodular appearances. On ultrasonography, SAM is a hypoechoic and heterogeneous tumor with a regular shape, well‐defined boundary, capsule, and posterior acoustic enhancement, which has a great variety of blood flow signals 2 . Computed tomography findings of SAM show an ovoid low‐density tumor with a slight or significant enhancement.…”
Section: Figurementioning
confidence: 99%
“…On ultrasonography, SAM is a hypoechoic and heterogeneous tumor with a regular shape, welldefined boundary, capsule, and posterior acoustic enhancement, which has a great variety of blood flow signals. 2 Computed tomography findings of SAM show an ovoid low-density tumor with a slight or significant enhancement. Additionally, magnetic resonance imaging has shown that SAM is a relatively well-circumscribed tumor with hypervascularity that shows an inner homogenous high signal intensity.…”
mentioning
confidence: 99%